Cemental composites with polyurethane and recycled polyvinyl chloride: The influence of industrial waste addition on flammability. Issue 8 (29th April 2021) - Marques, Diego Valdevino; Cremona Parma, Gabriel Oscar; Valezan, Igor Fagundes; de Aguiar, Ana Carolina; Mendonça, Bruno Afonso Büchele; Cruz Junior, Américo; da Silva, Luciano; Soriano Corral, Florentino; Sanchez, Saul; Barcelos, Ricardo Luis; Magnago, Rachel Faverzani
Abstract: In the construction industry, the large number of residues presents a challenge for recycling and the possibility of producing new materials. This study reported the effects of the addition of polyvinyl chloride (PVC) residues and cement/alumina trihydrate on the production of a fire‐resistant thermal‐acoustic insulation material. The composites were verified by scanning electron microscopy, the polyurethane (PU) cells were maintained with the addition of PVC, cement, and trihydrate alumina. The reduction in compressive strength for boards with 50% PVC waste as a replacement for the PU raw material. The boards showed the composites' conductivity coefficient was lower than that of the perforated brick and combustion deceleration up to flame extinction in the flammability test (UL94) because of the PVC/cement/alumina trihydrate. They also presented cost savings (~57%) and carbon dioxide emissions (~49%) from the raw material, contributing to developing a less predatory and socio‐environmentally responsible industry. Abstract : Composites with 50% polyvinyl chloride (PVC) waste replacing primary inputs. The PVC residue contributed positively as a flame retardant. Cement and alumina trihydrate reduce the release of flue gases.